Properties Of Silver Filled Epoxy Composites For Electrical Conductive Adhesive Applications - Shariff, Khairul Anuar (2011)
The study aims to improve the electrical conductivity, thermal and flexural properties of silver filled epoxy composites for electrical conductive adhesive applications. In order to achieve the main aim, few parameters such as effect of hardener content, comparison on two types of silver filler and hybrid silver filled epoxy composites were investigated.